Application of Cognitive Behavioral Therapy for Employee Retention - Padmasiri, M.K Dinithi; Jayatilake, L.V.K. (Asian Journal of Empirical Research, 2017)
The purpose of this paper is to identify whether the application of Cognitive Behavioral Therapy (CBT) affects employee retention during the exit interviews. Thus, this study is mainly qualitative in nature where the sample size was 20 machine operators who decided to resign during the period of April to May 2016. In order to collect data, researchers applied convenience-sampling techniques with in-depth semi-structured interviews. As a counselling technique, CBT was applied for eight machine operates at the exist interview and six employees were retained. However, after the counselling sessions, two employees were left the institution. This study proposes to apply Rational Emotional Behavioral Therapy, and modifying dysfunctional thinking and behavior as CBT techniques during the exit interview or any appropriate time before the employee leaving in order to retain employees. This study contributes to the knowledge as yet; CBT is not proposed to apply and not tested empirically at the exit interview time in order to retain employees, other than conducting exit interviews to investigate reasons for employee leaving.